ABOUT ASSUMPTION UNIVERSITY (AU) - Assumption University (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The St. Gabriel Foundation, a worldwide organization founded in France in 1705, is responsible for the establishment and administration of Assumption University. The Foundation has been dedicated to education and philanthropic activities in Thailand for more than 100 years and it now operates 14 educational institutions providing all levels of education. Assumption School of Business was initially founded in 1969, and in 1972 it became Assumption Business Administration College (ABAC). In 1975 the Ministry of University Affairs accredited ABAC and later in 1990 it was accredited as a fully-fledged university, and renamed as Assumption University (AU). The University is administered by a Council which takes policy initiatives and provides guidance for long-term planning and the formulation of control procedures. Today, AU is considered the leading private university in Thailand in the fields of Business, Management and Information Technology as demonstrated by the placement of many of its graduates in key management and technological positions in industry, government, banking and multinational conglomerates worldwide. The University’s curriculum is patterned after the American semester hour credit system and most textbooks are similar to those used in international universities. Graduates receive an education that is both globally marketable and flexible, leading to highly productive careers within the various sectors of society from which the students come and to which they aspire tobe. CAMPUSES Assumption University maintains three campuses: the original campus located at Hua Mak, the new campus at Suvarnabhumi, and the City Campus, which is located on the 14th floor of the ZEN Department Store @ Central World in the center of Bangkok. Hua Mak Campus The original campus is a compact, vertical campus comprising 17 buildings with the tallest having a total of 16 floors. A small lake surrounded by lush gardens and seating is a focal point of beauty and tranquility. Food, convenience and service shops to support student needs surround the campus. This will become the home of postgraduate faculties in the near future. The Suvarnabhumi Campus The Suvarnabhumi Campus, constructed as a “University in a Park”, comprises 200 acres of a beautifully landscaped assembly of mixed architecture surrounded by lush, tropical gardens and trees. Designed to host the university’s undergraduate degree programs, it offers everything: a meeting/exhibition center, hotel, non-coeducational dormitories, a magnificent chapel, a museum, three academic halls, and much more. The centerpiece of the campus is the Cathedral of Learning, a 39-storey tower which houses student support services, the library, reception halls, seminar rooms and offices. Transportation between the two campuses is convenient and inexpensive. Shuttles run throughout the day between various points in Bangkok and the Suvarnabhumi Campus